Priests of the law : Roman law and the making of the common law's first professionals - McSweeney, Thomas J. (Oxford : Oxford University Press, 2020)
This volume examines the development of legal professionalism in the early English common law, with specific reference to the 13th-century treatise known as Bracton and to its likely authors.
This edition previously issued in print: 2019.
Includes bibliographical references and index.
Specialized.
Description based on online resource; title from home page (viewed on January 13, 2020).
Keywords: Law -- England -- History -- To 1500.; Practice of law -- England -- History -- To 1500.; Roman law; Common law -- History; Law; Laws of specific jurisdictions & specific areas of law